Pengaruh Progressive Muscle Relaxation terhadap Penurunan Tingkat Keletihan Gagal Ginjal Kronik yang Menjalani Hemodialisa - Monika Izza Nasrulloh; Resti Yulianti Sutrisno; Purnomo Widiyanto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Chronic Kidney Failure (CKD) is a progressive and irreversible disease characterized by a decrease in the glomerular filtration rate (GFR). In this disease, uremia impairs the kidney's ability to maintain metabolism and water and electrolyte balance. Fatigue is one of the most common symptoms in patients undergoing hemodialysis which impacts quality of life. Progressive muscle relaxation is a type of non-pharmacological nursing intervention that can be used to treat fatigue in CKD patients undergoing hemodialysis. The aim of this research is to determine the application of progressive muscle relaxation therapy to fatigue in CKD patients undergoing hemodialysis therapy. The research design used is a case report. The instrument used to measure the level of fatigue is the Functional Assessment Chronic Illness Therapy (FACIT) fatigue scale. The intervention was carried out for ten to fifteen minutes over three days in the hospital hemodialysis unit and four days at the patient's home. Evaluation of respondents' level of fatigue was carried out on days 1, 5, and 8. The results of this study showed that the fatigue level score after intervention on day 1 was 16 (severe category), the score on day 5 was 20 (moderate category), and day 8 was 24 (moderate category). It can be concluded that progressive muscle relaxation therapy can reduce fatigue in CKD patients undergoing hemodialysis. The results of this research can be applied independently by nurses for CKD patients undergoing hemodialysis to reduce fatigue levels.